2005
DOI: 10.1080/00103620500303913
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes of Shoot Nitrogen Concentrations and15N/14N Ratios in Common Reed in a Constructed Wetland

Abstract: Nitrogen (N) concentrations and stable N isotope abundances (d 15 N) of common reed (Phragmites australis) planted in a constructed wetland were measured periodically between July 2001 and May 2002 to examine their seasonal variations in relation to N uptake and N translocation within common reed. Nitrogen concentrations in P. australis shoots were higher in the growing stage (7.5 to 24.8 g N kg 21 ) than in the senescence stage (4.2 to 6.8 g N kg 21 ), indicating N translocation from shoots to rhizomes. Meanw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
4
2
Order By: Relevance
“…Kolb and Evans [97] and Garten [107] found no significant differences in the δ 15 N values of living and abscised leaves, which suggested a lack of 15 N discrimination with N remobilization. Conversely, several other studies have found older or senescent plant leaves to be characterized by higher δ 15 N values, which has been attributed to a kinetic isotopic fractionation associated with N catabolism and reallocation [108][110]. We observed no significant difference between leaf δ 15 N at 75 d and 115 d for the control group, suggesting that under normal circumstances, there is no significant fractionation associated with N remobilization from leaves for this variety of maize.…”
Section: Resultscontrasting
confidence: 73%
“…Kolb and Evans [97] and Garten [107] found no significant differences in the δ 15 N values of living and abscised leaves, which suggested a lack of 15 N discrimination with N remobilization. Conversely, several other studies have found older or senescent plant leaves to be characterized by higher δ 15 N values, which has been attributed to a kinetic isotopic fractionation associated with N catabolism and reallocation [108][110]. We observed no significant difference between leaf δ 15 N at 75 d and 115 d for the control group, suggesting that under normal circumstances, there is no significant fractionation associated with N remobilization from leaves for this variety of maize.…”
Section: Resultscontrasting
confidence: 73%
“…No clear pattern in Δ 15 N other plant part-leaf was observed, likely because of confounding factors such as differences in root morphology, depth and distribution, microhabitat, mycorrhizal associations and growing stage. The root crowns examined here have higher N contents ( Fig 5 ) and δ 15 N ( Fig 3 ) than other plant parts; this difference is statistically significant for N content, but not for δ 15 N. As discussed earlier, nitrogen contents of different plant parts commonly show variations between active growing and senescent stages in herbaceous plants [ 114 , 115 ]. The higher N content of the root crowns in this study is best explained by N re-allocation from leaves to below ground parts late in the growing season.…”
Section: Discussionmentioning
confidence: 58%
“…In reed species, including P. australis, relocation of N and P from aboveground organs into belowground organs has been observed to occur after flowering and from belowground organs to aboveground organs in spring at the beginning of the vegetation period (Davis & van der Valk, 1983;Choi et al, 2005). In sampling site K1 on Paljassaare, N accounted for 3.75% DM in the leaf blades of P. australis in August and for 1.73% in October, so a 2.2-fold decrease was observed.…”
Section: Resultsmentioning
confidence: 98%
“…The peninsula is a favourable habitat for bird species of all-European importance and other protected animal and plant species. In 2005, with the Estonian Government Regulation No. 144 (RTI 07.07.2005, the Paljassaare Special Protection Area with an area of 277 hectares was placed under legal protection as Paljassaare Special Conservation Area (Paljassaare hoiuala kaitsekorralduskava, 2006(Paljassaare hoiuala kaitsekorralduskava, -2008.…”
Section: Introductionmentioning
confidence: 99%